(3QGMI GdCQhGM aj GdMTjT hGdQGMs - (3Jbj GdOjf GdHOQj, GdOeTbjs
(3ChdgG (B:s
(3GdMeO ddg GdPi MQe Ydi YHOg GdJbi cd eG jScQ GdfaS hHYO abO SCdfi ef CeQg eWGY s
(3BNQgG (B:s
(3cCfeG NhUg Ydjg RHQLO eKeQ YbjbG s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGdKs
(3HChdgG hba jYhOs
(3SfI (B1316 (3g` hHBNQ UaMGJgG JYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B4 - (3U (B7 s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
Keywords: (3GdCOHs